Optimization of the Black Garlic Processing Method and Development of Black Garlic Jam Using High-Pressure Processing - Wen-Chang Chang; Wen-Chun Lin; She-Ching Wu (Foods, 2023)
Black garlic has many beneficial effects, and it has a less spicy flavor. However, its aging conditions and related products still need to be further investigated. The present study aims to analyze the beneficial effects under different processing conditions and utilize high-pressure processing (HPP) in the production of black garlic jam. The highest antioxidant activities, including the DPPH scavenging, total antioxidant capacity, and reducing power (86.23%, 88.44%, and A700 = 2.48, respectively), were observed in black garlic that had been aged for 30 days. Similarly, the highest total phenols and flavonoids were observed in black garlic that had been aged for 30 days (76.86 GAE/g dw and 13.28 mg RE/g dw, respectively). The reducing sugar in black garlic was significantly increased to about 380 (mg GE/g dw) after 20 days of aging. The free amino acids in black garlic were decreased time-dependently to about 0.2 mg leucine/g dw after 30 days of aging. For the browning indexes of black garlic, the uncolored intermediate and browning products were increased in a time-dependent manner and reached a plateau at day 30. Another intermediate product in the Maillard reaction, 5-hydroxymethylfurfural (5-HMF), was observed in concentrations that increased to 1.81 and 3.04 (mg/g dw) at day 30 and 40, respectively. Furthermore, the black garlic jam made by HPP was analyzed for its texture and sensory acceptance, showing that a 1:1.5:2 ratio of black garlic/water/sugar was the most preferred and was classified as “still acceptable”. Our study suggests suitable processing conditions for black garlic and outlines the prominent beneficial effects after 30 days of aging. These results could be further applied in HPP jam production and increase the diversity of black garlic products.